2012
DOI: 10.1258/ijsa.2011.011337
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 drug resistance at virological failure versus immunological failure among patients failing first-line antiretroviral therapy in a resource-limited setting

Abstract: Antiretroviral treatment failure has been defined by immunological failure (IF) in some resource-limited settings whereas defining by virological failure (VF) has been widely used in developed countries. There is limited comparison of the levels of HIV-1 drug resistance between using VF and IF for the diagnosis of treatment failure. A retrospective cohort study was conducted among HIV-1-infected patients failing first-line antiretroviral therapy (ART). Of 95 patients, median CD4 and HIV-1 RNA were 158 cells/mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Our findings were consistent with previous reports which showed that NNRTI RAMS were the most common, followed by NRTI and PI RAMs [6, 29, 30]. Our study also found that approximately one-third of the patients harboured multi-NRTI RAMs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were consistent with previous reports which showed that NNRTI RAMS were the most common, followed by NRTI and PI RAMs [6, 29, 30]. Our study also found that approximately one-third of the patients harboured multi-NRTI RAMs.…”
Section: Discussionsupporting
confidence: 93%
“…These studies demonstrated that the prevalence of RAMs in patients failing first-line ART ranged from 53 to 84% with 38–64% harbouring dual-class resistance [25]. The prevalence of RAMs in individuals experiencing first-line ART failure in Asia has ranged from 87 to 95% with 50–64% harbouring dual-class mutations [69]. …”
Section: Introductionmentioning
confidence: 99%
“…Most first-line failure data in this HIV subtype are reported from Thailand, with NNRTI and NRTI resistance of 89-95% and 42-58% in adults and 97% and 98% in children, respectively. 13,[22][23][24][25][26][27] Data on drug resistance in Cambodian children failing ART are limited. In a recent systematic review of first-line ART failure among children, 28 within 30 reviewed studies on 3,241 children, only 265 (8%) were from Cambodia and only 74 (2%) of those had genotypes available, some available only in poster form and after second-line ART failure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that by using methods other than VL to assess ART response, there may be a delay in switching to second-line ART which has been shown to be associated with mortality. Furthermore, patients with immunological failure were shown to have higher VL and higher rates of HIV drug resistance mutations compared to those with virological failure, which could impact second-line treatment options[13, 14]. As TAHOD sites are located in high and low-income countries[15], the frequency of VL testing in TAHOD sites varies substantially from an average of less than once per year to more than three times per year[3].…”
Section: Discussionmentioning
confidence: 99%